Ponasterone A and F, Ecdysteroids from the Arctic Bryozoan Alcyonidium gelatinosum - Østnes Hanssen, Kine; Isaksson, Johan; Glomsaker, Eirin; Andersen, Jeanette hammer; Hansen, Espen (Molecules, 2018)
Publisher's version allowed, licensed CC BY-NC-ND 4.0. Link to publisher's version: http://dx.doi.org/10.3390/molecules23061481 A new ecdysteroid, ponasterone F (1) and the previously reported compound ponasterone A (2) were isolated from specimens of the Arctic marine bryozoan Alcyonidium gelatinosum collected at Hopenbanken, off the coast of Edgeøya, Svalbard. The structure of 1 was elucidated, and the structure of 2 confirmed by spectroscopic methods including 1D and 2D NMR and analysis of HR-MS data. The compounds were evaluated for their ability to affect bacterial survival and cell viability, as well as their agonistic activities towards the estrogen receptors α and β. The compounds were not active in these assays. Compound 2 is an arthropod hormone controlling molting and are known to act as an allelochemical when produced by plants. Even though its structure has been previously reported, this is the first time a ponasterone has been isolated from a bryozoan. A. gelatinosum produced 1 and 2 in concentrations surpassing those expected of hormonal molecules, indicating their function as defence molecules against molting predators. This work adds to the chemical diversity reported from marine bryozoans and expanded our knowledge of the chemical modifications of the ponasterones